Establishing an auxin-inducible GFP nanobody-based acute protein knockdown system to mimic hypomorphic mutations during early medaka embryogenesis - Pakari, Kaisa; Jakab, Sevinç; Rasch, Johanna; Sánchez Salvador, Encarnación; Wittbrodt, Beate; Thiel, Christian; Wittbrodt, Joachim; Thumberger, Thomas (Biology open, 2025)
Creating hypomorphic mutations is crucial to study gene function in vivo, especially when null mutations result in (embryonic) lethality. This applies to enzymes involved in glycosylation that, when mutated in human patients, cause the disease congenital disorders of glycosylation (CDG). In order to resemble patient condition, it would be ideal to acutely modulate the proteins in question to directly interfere with protein levels of such essential enzymes. These methods offer to establish pathogenic enzyme levels resembling net enzyme activity reported in patients suffering from CDG, with phosphomannomutase 2-CDG (PMM2-CDG) as the most common form.We established an auxin-inducible acute protein knockdown system for the use in the teleost fish medaka (Oryzias latipes) by combining an improved degron (AID2) technology with an mAID-nanobody targeting endogenously GFP-tagged Pmm2 protein. We generated a fishline expressing a functional Pmm2-GFP fusion protein, by single copy integration of GFP into the pmm2 locus. Upon induction, the degron system efficiently reduced Pmm2-GFP levels and enzyme activity, recapitulating the activity level of the hypomorphic mutations associated with PMM2-CDG in patients. This broadly applicable approach enables the investigation of CDG disease mechanisms during early embryonic development through reduction of protein abundance, mimicking hypomorphic mutations and thus substantially expanding the range of the genetic toolbox.
Online veröffentlicht: 7. November 2025
Gesehen am 10.11.2025